Association between digestive diseases and sarcopenia among Chinese middle-aged and older adults: a prospective cohort study based on nationally representative survey - Cui, Guanghui; Li, Shaojie; Ye, Hui; Yang, Yao; Chu, Yingming; Jia, Xiaofen; Feng, Yue; Lin, Miaomiao; Zhang, Xuezhi (Frontiers in Nutrition, 2023)
Objectives: Patients with digestive diseases frequently suffer from sarcopenia. However, it is not clear whether digestive diseases are associated with sarcopenia. This study aims to explore the longitudinal association between digestive diseases and sarcopenia in middle-aged and older adults based on a nationally representative survey from China. Methods: We used a prospective cohort study including 7025 middle-aged and older adults aged ≥45 years from the 2011 and 2015 waves China Health and Retirement Longitudinal Study (CHARLS). Digestive diseases were identified using self-report. The assessment of sarcopenia was based on the Asian Working Group for Sarcopenia 2019 Consensus and included three components of muscle strength, physical performance, and muscle mass. Cox hazards regression was used to examine the association between digestive diseases and sarcopenia. Results: The prevalence of digestive diseases and the incidence of sarcopenia in middle-aged and older adults were 22.6% (95%CI=21.6%-23.6%) and 8.5% (95%CI=7.8%-9.1%). After adjusting for 15 covariates composed of three sets (demographic characteristics, lifestyles, and health status), digestive diseases were associated with a higher risk of sarcopenia (HR=1.241, 95%CI=1.034-1.490, P<0.05). The associations were more pronounced among men, older adults aged 60-79, rural residents, and married people. In addition, the association between digestive diseases and sarcopenia was robust in the sensitivity analysis. Conclusion: Digestive diseases were associated with an increased risk of sarcopenia in middle-aged and older adults aged ≥45 years. Early intervention of digestive diseases may help to reduce the incidence of sarcopenia in middle-aged and older adults.